Tratamientos alternativos de origen natural para las enfermedades de Chagas y Leishmaniasis (2021)
The present work is a review of the state of the art on the antiparasitic potential of extracts and / or metabolites from plants, propolis and chitosan, as therapy for Leishmaniasis and Chagas disease. Products of natural origin capable of attacking the causative agents of these pathologies were identified Trypanosoma cruzi and Leishmania spp. Based on this, a study was proposed as an alternative in the treatment of these conditions. In order to develop this project, a descriptive literature review of the last six years (2015-2021) was carried out in the main scientific databases. The results do not describe relevant cellular toxicity, but they do describe high antiparasitic activity of plant extracts, propolis, chitosan and chitosan nanoparticles, which present various phytochemical compounds. These act directly on parasites or on host cells, activating immune response signaling pathways.